Population dynamics between the mermithid Strelkovimermis spiculatus (Nematoda: Mermithidae) and the floodwater mosquito Ochlerotatus albifasciatus (Diptera: Culicidae) over time - María V. Micieli, Paula Risso, María F. Achinelly , M. de los Milagros Villar, Evangelina Muttis (2012)
We investigated the population dynamics of Strelkovimermis spiculatus in Ochlerotatus albifasciatus to determine the abiotic and biotic parameters involved in this host-parasite system. Weekly samplings performed from May 2007 through May 2010 in three ponds located in open areas of La Plata, Argentina revealed that parasitism by S. spiculatus in O. albifasciatus occurred throughout all seasons with differences in effectiveness among breeding habitats: A mosquito-larva reduction of 80.7% was observed in a habitat where 100% of the generations were infected by nematodes; an intermediate situation (a 41.9% reduction) involved a lower percentage of parasitism above 50% although nematode infection was likewise registered in 92.9% of the generations. Finally, a mosquito-larva reduction of 2.68% was recorded where only 46.0% of the generations were parasitized and at levels of nematode infection below 50%. We analyzed the effects of abiotic and biotic parameters on S. spiculatus infections. The floodedsurface area was the only variable significantly associated with percent infection. Infection prevalence correlated positively with the mean number of emerged nematodes per larva and with the S. spiculatus male-to-female ratio in each parasitized-mosquito generation. In conclusion, the frequency over time and levels of infection are key parameters in the regulation of mosquito populations by this mermithid